Kesalahan Siswa dalam Merepresentasikan Bilangan Pecahan pada Garis Bilangan - Nabilah Mansur (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
Middle school students are a tool for measuring student math literacy capabilities. Student errors need to be known to improve student math literacy skills. The purpose of this study is to explain students' mistakes in representing fractional numbers on the number line. The method of this research uses a qualitative approach with descriptive type. The study was conducted in class VIIIA SMP 4 Prabumulih on March 5, 2024 with 25 subjects of students. The instruments used are written tests and interviews. Based on exposure to the results of research and discussions, it can be concluded that students' mistakes occur because students represent the fractions with same denominator without concerning into the value of the fractions, students also represent the fractions’ numerator by sorting denominator.